Eugenia sulcata (Myrtaceae) Nanoemulsion Enhances the Inhibitory Activity of the Essential Oil on P2X7R and Inflammatory Response In Vivo - Bettina Quintanilha Magalhães; Francisco P. Machado; Paola S. Sanches; Bárbara Lima; Deborah Quintanilha Falcão; Natalia von Ranke; Murilo Lamim Bello; Carlos Rangel Rodrigues; Marcelo Guerra Santos; Leandro Rocha; Robson X. Faria (MDPI AG, 2022)
P2X7R is a purinergic receptor with broad expression throughout the body, especially in immune system cells. P2X7R activation causes inflammatory mediators to release, including interleukin-1β (IL-1β), the processing and release of which are critically dependent on this ion channel activation. P2X7R's therapeutic potential augments the discovery of new antagonistic compounds. Thus, we investigated whether the Eugenia sulcata essential oil could block P2X7R activity. The essential oil (ESO) dose-dependently inhibited ATP-promoted PI uptake and IL-1β release with an IC50 of 113.3 ± 3.7 ng/mL and 274 ± 91 ng/mL, respectively, and the essential oil nanoemulsion (ESON) improved the ESO inhibitory effect with an IC50 of 81.4 ± 7.2 ng/mL and 62 ± 2 ng/mL, respectively. ESO and ESON reversed the carrageenan-activated peritonitis in mice, and ESON exhibited an efficacy higher than ESO. The majority substance from essential oil, β-caryophyllene, impaired the ATP-evoked PI uptake and IL-1β release with an IC50 value of 26 ± 0.007 ng/mL and 97 ± 0.012 ng/mL, respectively. Additionally, β-caryophyllene reduced carrageenan-induced peritonitis, and the molecular modeling and computational simulation predicted the intermolecular interactions in the P2X7R situs. In silico, results indicated β-caryophyllene as a potent allosteric P2X7R antagonist, although this substance may present toxic effects for humans. These data confirm the nanoemulsion of essential oil from E. sulcata as a promisor biotechnology strategy for impaired P2X7R functions and the inflammatory response.